Real-Time Induction of Macrophage Apoptosis, Pyroptosis, and Necroptosis by Enterococcus faecalis OG1RF and Two Root Canal Isolated Strains - Chi, Danlu; Lin, Xinwei; Meng, Qingzhen; Tan, Jiali; Gong, Qimei; Tong, Zhongchun (Frontiers in Cellular and Infection Microbiology, 2021)
To investigate the effects of two Enterococcus faecalis root canal isolated strains (CA1 and CA2) and of the OG1RF strain on apoptosis, pyroptosis, and necroptosis in macrophages. The virulence factors of E. faecalis CA1 and CA2 pathogenic strains were annotated in the Virulence Factors Database (VFDB). E. faecalis CA1, CA2, and OG1RF strains were used to infect RAW264.7 macrophages (MOI, 100:1). We assessed the viability of intracellular and extracellular bacteria and of macrophages at 2, 6, and 12 h post-infection. We used a live cell imaging analysis system to obtain a dynamic curve of cell death after infection by each of the three E. faecalis strains. At 6 and 12 h post-infection, we quantified the mRNA expression levels of PANoptosis-related genes and proteins by RT-qPCR and western blot, respectively. We identified ultrastructural changes in RAW264.7 cells infected with E. faecalis OG1RF using transmission electron microscopy. We found 145 and 160 virulence factors in the CA1 and CA2 strains, respectively. The extracellular CA1 strains grew faster than the CA2 and OG1RF strains, and the amount of intracellular viable bacteria in the OG1RF group was highest at 6 and 12 h post-infection. The macrophages in the CA1 infection group were the first to reach the maximum PI-positivity in the cell death time point curve. We found the expressions of mRNA expression of caspase-1, GSDMD, caspase-3, MLKL, RIPK3, NLRP3, IL-1β and IL-18 and of proteins cleaved caspase-1, GSDMD, cleaved caspase-3 and pMIKL in the macrophages of the three infection groups to be upregulated (P<0.05). We detected ultrastructural changes of apoptosis, pyroptosis, and necroptosis in macrophages infected with E. faecalis. The three E. faecalis strains induced varying degrees of apoptosis, pyroptosis, and necroptosis that were probably associated with PANoptosis in macrophages. The E. faecalis CA1 strain exhibited faster growth and a higher real-time MOI, and it induced higher expression levels of some PANoptosis-related genes and proteins in the infected macrophages than the other strains tested.